Adsorption of U(VI) ions from aqueous solution using nanogoethite powder. Issue 1 (March 2019) - Zhang, Lijiang; Zhang, Xiaowen; Lu, Qian; Wu, Xiaoyan; Jiang, Tianjiao; Mi, Li; Peng, Ying
Goethite is a stable and widespread mineral present in soil with many uses, and it affects the transportation and immobilization of heavy metals in solution. Nanogoethite was synthesized by a chemical precipitation method and used to batch adsorb U(VI) in solution. Adsorption experiments were used to understand the role of nanogoethite in controlling the U(VI) adsorption behavior in soil. The morphology and the crystallinity of nanogoethite were characterized by scanning electron microscopy and wide-angle X-ray powder diffractometry, respectively. The results showed that the crystallinity of nanogoethite after the adsorption of uranium did not change, but small particles appeared on the surface of the scales. The surface area was determined from N2 adsorption–desorption experiments using the Brunauer–Emmett–Teller to be 81.86 m 2 /g. The effects of factors such as the contact time, pH, adsorbent dosage, and the initial concentration of uranium on the adsorption of U(VI) were investigated. The experimental results showed that nanogoethite removed over 85% of the U(VI) in an aqueous 5.0 mg/L U(VI) solution at pH 4.0 and at 298 K. The pseudo-second-order model was used to simulate the adsorption process. The results show that chemisorption plays a major role in the adsorption process. The results of this study suggest that nanogoethite may play a significant role in controlling the migration and transfer of U(VI) in the soil, thus controlling the presence of U(VI) in soil.